"It won't be any good to have democracy if we don't have a country": Climate change and the politics of synecdoche in the Maldives. (November 2015) - Hirsch, Eric
Highlights: From 2008–2012, the Maldives claimed to be the world's living index of climate change. Internally, claiming geopolitical identity was also a state-making device. Amateur experiments and climate policy critique became forms of democratic action. Experiences of environmental vulnerability are rooted in their political contexts. Abstract: Critical attention has recently turned to the climate change "synecdoche": a place uniquely exposed to the environmental consequences of climate crisis, such as sea-level rise, that becomes a stand-in for the global crisis as a whole and a harbinger of more widespread disaster. The Maldives, which scientists, politicians, and activists predict could be completely submerged by 2100, filled that role between the 2008 inauguration of Mohamed Nasheed, the country's first democratically elected president after years of authoritarian rule, and his 2012 ouster. This ethnography of the Maldivian challenge to climate change asks how claiming a geopolitical identity as the world's "canary in the coalmine" fostered an emerging internal political culture. I argue that arming climate change solutions became a state-making device in the Maldives, whose fragile coral atoll ecosystem itself became the synecdoche of a young democracy. Between 2008 and 2012, how was environmental knowledge creation understood as a democratic activity? To answer this question, I draw on ethnographic interview testimony and participant-observation in Malé, the Maldivian capital, with politicians, activists, and city residents, as well as an analysis of the Nasheed administration's public rhetoric. The article centers on the case of Bluepeace, the country's oldest environmental NGO, which has seen significant international publicity. Following Bluepeace's efforts to help the Maldives achieve carbon neutrality by 2020—part of Nasheed's plan to end global climate change through exemplary national sacrifice—this article finds that climate problem solving and democracy were put to work for one another through small-scale mitigation and adaptation experiments.